Integrated physiological and weighted gene co-expression network analysis reveals the hub genes engaged in nitrate-regulated alleviation of ammonium toxicity at the seedling stage in wheat (Triticum aestivum L.) - Li, Liuyin; Zang, Xiuzhi; Liu, Jianbo; Ren, Jinfeng; Wang, Zhenlin; Yang, Dongqing (Frontiers in Plant Science, 2022)
Wheat has a specific preference for NO3- and shows toxicity symptoms under high NH4+ concentrations. Increasing the nitrate supply may alleviate ammonium stress. Nevertheless, the mechanisms underlying the nitrate regulation of wheat root growth to alleviate ammonium toxicity remain unclear. In this study, we integrated physiological and weighted gene co-expression network analysis (WGCNA) to identify the hub genes involved in nitrate alleviation of ammonium toxicity at the wheat seedling stage. The results showed that sole ammonium treatment (Na) increased the lateral root number but reduced root biomass. Increasing the nitrate supply significantly increased the root biomass. Increasing nitrate levels decreased abscisic acid (ABA) content and increased auxin (IAA) content. Furthermore, we, identified two modules (blue and turquoise) using transcriptome data that were significantly related to root physiological growth indicators. TraesCS6A02G178000 and TraesCS2B02G056300 were identified as hub genes in the two modules which coded for plastidic ATP/ADP-transporter and WRKY62 transcription factors, respectively. Additionally, network analysis showed that in the blue module, TraesCS6A02G178000 interacts with downregulated genes that coded for indolin-2-one monooxygenase, SRG1, DETOXIFICATION, and wall-associated receptor kinase. In the turquoise module, TraesCS2B02G056300 was highly related to the genes that encoded ERD4, ERF109, CIGR2, and WD40 proteins, and transcription factors including WRKY24, WRKY22, MYB30, and JAMYB, which were all upregulated by increasing nitrate supply. These studies suggest that increasing the nitrate supply could improve root growth and alleviate ammonium toxicity through physiological and molecular regulation networks, including ROS, hormonal crosstalk, and transcription factors.